2019
DOI: 10.1021/acs.energyfuels.9b00179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Liquid Impregnation in Highly Water-Stable Metal–Organic Frameworks, Covalent Organic Frameworks, and Carbon-Based Adsorbents for Post-combustion Flue Gas Treatment

Abstract: In this work, a comparative study on water-stable microporous adsorbents is conducted computationally in the quest of a suitable adsorbent for post-combustion CO2 capture. In this regard, three metal–organic frameworks (MOFs), two covalent organic frameworks (COFs), and a single-wall carbon nanotube (SWCNT) are investigated under the same flue gas conditions. The simulation results show that the pure component adsorption capacity for CO2 follows the order SWCNT > InOF-1 > COF-300 > UiO-66 > COF-108 > ZIF-8 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…N 2 ,61 or both[66][67][68] was also achieved in other studies. The schematic of one of these adsorbents namely [C 2 mim][SCN]@Cu-BTC was shown in Figure3and ILs were present in both pores and surface of supports.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…N 2 ,61 or both[66][67][68] was also achieved in other studies. The schematic of one of these adsorbents namely [C 2 mim][SCN]@Cu-BTC was shown in Figure3and ILs were present in both pores and surface of supports.…”
supporting
confidence: 75%
“…53 There is no doubt that both ILs and supports play an important role in CO 2 separation for supported IL adsorbent. 61 [Tf 2 N]@ZIF-8 showed stronger interaction with CO 2 , resulting in better CO 2 separation performance than other IL@ZIF-8 with the same anion.…”
Section: Supported Il Adsorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work showed that these ILs are capable of separating CO 2 from other gases such as CH 4 and N 2 131 . Therefore, RTILs have been thoroughly investigated in the application of natural gas purification 132,133 and flue gas treatment 134‐136 …”
Section: Ionic Liquid (Il)mentioning
confidence: 99%
“…Zhang et al 20 computationally studied SO 2 capture from SO 2 /CO 2 and SO 2 /N 2 mixtures using porous aromatic frameworks (PAFs) where it has been concluded that the incorporation of the functional groups (−CH 3 , −CN, −COOH, −COOCH 3 , −OH, −OCH 3 , −NH 2 , and −NO 2 ) into PAF-1 boosts the SO 2 selective behavior of the materials especially below 10 bar. Maurya and Singh 34 simulated the SO 2 adsorption in several adsorbents (COF-108, COF-300, single-walled carbon nanotube (SWCNT), InOF-1, UiO-66, and ZIF-8) around ambient conditions where the SO 2 uptakes of UiO-66 and ZIF-8 (∼5 mol/kg) are found to be several folds lower than that of SWCNT (∼23 mol/kg). Li et al 9 performed grand canonical Monte Carlo (GCMC) simulations to investigate the SO 2 capture from SO 2 /CO 2 and SO 2 /N 2 mixtures using UiO-66 and its functionalized variants where it has been concluded that UiO-66-(COOH) 2 and UiO-66-COOH exhibit two of the highest adsorption selectivities at low pressures (SO 2 /CO 2 and SO 2 /N 2 selectivity higher than ∼40 and 3000, respectively).…”
Section: Introductionmentioning
confidence: 99%